Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-11-27T19:36:30+01:00
Propiedades:

(*)  d c/dx = 0 , si c , es una constante
(*) d Cos(u) /dx =  -Sen(u) . u'
(*) d Sen (u)/dx = Cos(u) . u'
(*) d ln(u)/dx = u' / u
(*) d u^n/dx = n u^{n-1}. u'
(*) d f(x) + g(x) + h(x) + ... /dx = [f(x)]' + [g(x)]' + [h(x)]' + ...
(*) d [f(x)/ g(x) ] / dx = [ f(x)]' . g(x) -  [g(x)]' f(x)
                                            g²(x)

Entonces:


a) f(x)= 3x + cos x - 5 In 3


Derivando:

f'(x) = 3(1) x^{1-1} + (-senx)

f'(x) = 3  - Senx


b) f(x)= sen x + 5 cos x - e^4

Derivando:

f'(x) = cos(x) + 5 (-senx )

f'(x) =  cos(x) - 5sen(x)


c) f(x)= (x^4 - 3^3) * ln x

Derivando:

f'(x) = [ 4x³  - 0 ]  *  (1/x)

f'(x) = 4x³/ x = 4x²


d) f(x)= (3x^4 +1) / (cos x)

Derivando:

f'(x) =  [3x^4 + 1 ]' . Cos(x)  - [cosx]' . (3x^4 + 1)
                        Cos²x

f'(x) = 12x³ Cosx   - (-senx) (3x^4 + 1)
                   cos²x

f'(x) = 12x³ Cosx + Senx(3x^4 + 1)
                        cos²x


Eso es todo1!